PENGARUH MEDIA PEMBELAJARAN PREZI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SENI BUDAYA BIDANG SENI RUPA DI KELAS XI MIA SMA N 1 KOTO XI TARUSAN - Fajar Faulana Putra; Ramalis Hakim (Serupa The Journal of Art Education, 2020)
This study aims to determine whether there is an effect of Prezi's Learning Media and Learning Motivation on the Learning Outcomes of Cultural Arts in the Arts in Class X Mia SMA N 1 Koto XI Tarusan. The subjects of the study were students of class X Senior High School 1 Koto XI Tarusan. This study used a quasi-experimental research method (quasi-experimental) with a 2 x 2 research design. The data was collected through a learning motivation questionnaire instrument and a learning outcome test to see the difficulty index, distinguishing power and rehabilitation. The data analysis technique used is descriptive processing stage (research subject) and inductive analysis using the SPSS v program. 16.The results of the study, it was concluded that the learning outcomes of cultural arts (fine arts) using Prezi learning media in the experimental class of X Mia 3 class students were higher than the control class using conventional methods of students of class X Mia 4 at Koto 1 Public Senior High School. XI Tarusan.Keywords: Prezi Learning Media, Cultural Arts, Fine Arts.